2016
DOI: 10.4143/crt.2015.381
|View full text |Cite
|
Sign up to set email alerts
|

TRIM29 Overexpression Promotes Proliferation and Survival of Bladder Cancer Cells through NF-κB Signaling

Abstract: PurposeTRIM29 overexpression has been reported in several human malignancies and showed correlation with cancer cell malignancy. The aim of the current study is to examine its clinical significance and biological roles in human bladder cancer tissues and cell lines.Materials and MethodsA total of 102 cases of bladder cancer tissues were examined for TRIM29 expression by immunohistochemistry. siRNA and plasmid transfection were performed in 5637 and BIU-87 cell lines. Cell Counting Kit-8, flow cytometry, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…The tumor suppressor PDCD4 is often down-regulated in several malignancies, and its protein expression could be modulated by miR-21, indicating that PDCD4 down-regulation is a reliable biomarker for early-stage squamous cell esophageal neoplasia [29] In addition, compared to the normal group, NF-κB and TNF-α expression and the apoptosis rates were all increased. The NF-κB/TNF-α signaling pathway has been reported to promote cancer cell growth, angiogenesis, invasion, and eventually metastasis in many human tumors [30, 31]. As an important transcription factor, NF-κB is responsible for a variety of biological processes that participate in the transcription of proinflammatory genes, thus mediating cellular inflammatory responses, including the elevated expression of chemokines and cytokines [32].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor PDCD4 is often down-regulated in several malignancies, and its protein expression could be modulated by miR-21, indicating that PDCD4 down-regulation is a reliable biomarker for early-stage squamous cell esophageal neoplasia [29] In addition, compared to the normal group, NF-κB and TNF-α expression and the apoptosis rates were all increased. The NF-κB/TNF-α signaling pathway has been reported to promote cancer cell growth, angiogenesis, invasion, and eventually metastasis in many human tumors [30, 31]. As an important transcription factor, NF-κB is responsible for a variety of biological processes that participate in the transcription of proinflammatory genes, thus mediating cellular inflammatory responses, including the elevated expression of chemokines and cytokines [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more accurate indices for clinical staging, treatment and prognosis of bladder cancer are urgently required (4,5). The occurrence and development of bladder cancer is the result of the combined action of several types of pathways, which involve various mRNA and microRNA (miRNA or miR) molecules (6,7). The activation of the vascular endothelial growth factor C (VEGF-C) signaling pathway is closely associated with bladder cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…33,43,44 In addition to its ability to inhibit tumour suppressors, ATDC also exerts its oncogenic role through inducing the activation of oncogenic signalling pathways, such as nuclear factor-κB (NF-κB) and Akt. 28,45,46 Notably, the regulatory effect of Nevertheless, our study revealed that ATDC contributes to HCC progression associated with the regulation of GSK-3β/Wnt/β-catenin signalling.…”
Section: Discussionmentioning
confidence: 69%
“…ATDC is reported to promote tumour progression by inhibiting tumour suppressors including phosphatase and tensin homolog deleted on chromosome ten (PTEN) and p53 . In addition to its ability to inhibit tumour suppressors, ATDC also exerts its oncogenic role through inducing the activation of oncogenic signalling pathways, such as nuclear factor‐κB (NF‐κB) and Akt . Notably, the regulatory effect of ATDC on the activation of Wnt/β‐catenin signalling during tumour progression has been highlighted in recent years.…”
Section: Discussionmentioning
confidence: 99%